Model-based behavioral causality analysis of handball with delayed transfer entropy - Itoda, K.; Watanabe, N.; Takefuji, Y. (Procedia - Computer Science, 2015)
In goal-type ball games, such as handball, basketball, hockey or soccer, teammates and opponents share the same field. They switch dynamically their behaviors and relationships based on other players` behaviors or intentions. Interactions between players are highly complicated and hard to comprehend, but recent technological developments have enabled us to acquire positions or velocities of their behaviors. We focus on handball as an example of goal-type ball games and analyze causality between teammates` behaviors from tracking data with Hidden Semi-Markov Model (HSMM) and delayed Transfer Entropy (dTE). Although `off-the-ball` behaviors are a crucial component of cooperation, most research tends to focus on `on-the-ball` behaviors, and relations of behaviors are only known as tacit knowledge of coaches or players. In contrast, our approach quantitatively reveals player's relationships of `off-the-ball` behaviors. The extracted causal models are compared to the corresponding video scenes, and we claim that our approach extracts causal relationships between teammates` behaviors or intentions and clarifies roles of the players in both attacking and defending phase.